Pengaruh Kualitas Produk, Citra Merek Dan Harga Terhadap Keputusan Pembelian Produk 3second (Studi Kasus Pada Store 3second Jl Majapahit Mojokerto) - Tri Anggun Melen Novari; Imam Baidlowi; Toto Heru Dwihandoko (STIKes Ibnu Sina Ajibarang, 2023)
This study aims to determine the effect of product quality, brand image and price on purchasing decisions for 3Second products (Case Study at the 3Second store, Jl Majapahit Mojokerto). The type of research used is quantitative research based on the philosophy of positivism, used to examine certain populations or samples, data collection uses research instruments, data analysis is quantitative or statistical, which aims to test the established hypotheses. The data sources used in this study are primary data and secondary data, primary data comes from the results of online questionnaire respondents using a Likert scale, while secondary data comes from journals, analyzing books, online media and sources related to this research and existed before. The population in this study were consumers who had purchased 3Second products at least once at the 3Second store Jl Majapahit, Mojokerto, with a total sample of 75 respondents, using the Hair et al formula. This study uses a sampling technique, namely non-probability sampling using purposive sampling method, which means determining the sample using certain considerations. Data processing in this study includes validity test, reliability test, classic assumption test, multiple linear regression test, coefficient of determination test (R2), beta coefficient test, T test and F test. The results of this study indicate that product quality has a partial effect on decisions purchases of (2.899 > 1.993). Brand image has a partial and positive effect on purchasing decisions (2.953 > 1.993). And price also has a partial and positive effect on purchasing decisions of (3.179 > 1.993). Then for the F test which shows that product quality, brand image and price simultaneously influence purchasing decisions by (13.770 > 3.12) and get a significance value of 0.000.